Formation of Family Relations in Islam (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The family is a factor that ensures the continuity of generations, values, customs and traditions, as well as the transfer of the spiritual heritage of our people from generation to generation. Because of this, family relations and the upbringing of young people have always been one of the urgent social problems, and the issue of its support has been in the constant attention of our state.